Oil Palm Smallholders Entrepreneurs And Financial Literacy: Technology Adoption - Mara Ridhuan Che Abdul Rahman; Ummu Ajirah Abdul Rauf; Suguna Sinniah (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study explores the relationship between financial literacy and business performance among oil palm smallholder entrepreneurs in Malaysia, emphasizing the role of technology in improving financial practices. Many smallholders earn less than RM2000 per month, largely due to low financial literacy, which hinders effective financial management and business sustainability. Financial literacy is crucial for accessing financing and making informed financial decisions. Data were collected from 1,500 smallholders across six territories in Malaysia, with a 14.4% response rate. Structural Equation Modeling (SEM) revealed a positive correlation between financial literacy and improved financial practices, leading to better business outcomes, including enhanced access to bank loans and government grants. The study also highlights the transformative potential of digital technologies, such as mobile banking and financial education apps, in bridging financial literacy gaps. The findings suggest that targeted financial literacy programs and the adoption of digital tools can significantly enhance smallholders' financial management and business performance. This has important implications for policymakers and financial institutions in promoting rural economic development and sustainable entrepreneurship within the agricultural sector.